The Prevalence Description of Stunting among Toddlers - Luluk Khusnul Dwihestie; Luluk Rosida (LPPM STIKES KENDAL, 2020)
Growth is an indicator of a child's health, nutritional status, and genetic background. Currently, the problem of nutrition in children under five is stunting or often known as short toddlers. In 2017, the highest prevalence of children under five in Special Region of Yogyakarta occurred in Sleman district, namely 20.60%. Moyudan Primary Health Care, Sleman Regency, is 1 of 10 Public Health centers where there were still high numbers of children under five with stunting. The impact of stunting is not only a disruption of children's physical growth, but also affects the pattern of children's brain growth. This study aims to determine the prevalence of stunting under five. This type of observation was descriptive research. The population of all children under five who were stunted and were in the working area of ​​ Moyudan Primary Health Care of Sleman Yogyakarta. The sampling with total sampling technique, obtained 1,770 stunting toddlers. Data collection used secondary data, namely medical records. Univariate data analysis with frequency distribution. Based on the research results indicated that the description of nutritional status in Sumber Agung village, the working area of ​​Moyudan Primary Health Care, Sleman Yogyakarta, in 2019, namely 1.88% male toddlers and 1.5% very short female toddlers. Sumber Rahayu village, there were 1.7% male and 0.63% and very short female toddlers. Sumber Rahayu village had 1.43% male toddlers and 0.52% female toddlers. Sumber Sari village contained 2.01% male toddlers and 1.02% very short female toddlers.